2018
DOI: 10.17221/43/2018-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of persistent right aortic arch in a cat and three dogs

Abstract: We here report the diagnosis and surgical outcomes of a cat and three dogs with persistent right aortic arch causing oesophageal enlargement. The chief complaint in all cases was regurgitation just after solid food intake. Barium oesophagographic examinations revealed enlarged oesophaguses cranial to the heart and strictures due to arteriosus ligament constriction of the oesophagus. Surgical correction was carried out using left fourth intercostal thoracotomy and severance of the ligamentum arteriosum. The cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…However, it was concluded that early and accurate diagnosis of patients is as important as operative care to ensure the well-being of the patient. Calıskan et al reported that the studies were limited due to the very rare occurrence of vasculer ring anomalies (Caliskan et al, 2018). Therefore, two cases were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was concluded that early and accurate diagnosis of patients is as important as operative care to ensure the well-being of the patient. Calıskan et al reported that the studies were limited due to the very rare occurrence of vasculer ring anomalies (Caliskan et al, 2018). Therefore, two cases were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case study of 20 cats diagnosed with VRAs, 85% (17/20) had PRAA as the primary VRA, with four of these cats presenting with concurrent aberrant left subclavian artery 7 . A total of 43 other cases (that the authors are aware of) of VRAs in cats has been described in scientific literature dating as far back as 1960 1–3,5,6,8–28,32–33,36,37 . Of these cases, 60% (25/43) was diagnosed with a simple PRAA, and a further 12% (5/43) with PRAA and an aberrant left subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular ring anomaly (VRA) refers to the abnormal development of the embryonic great vessels and their associated branches 1–4 . Several different types of VRAs have been described in humans and various animals, including cats and dogs 1,2,4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Konventionell erfolgt der Zugang linksseitig über die laterale Thorakotomie im 4. Interkostalraum [28]. Nach Eröffnung des Thorax werden die Lungenlappen vorsichtig verlagert, das Mediastinum eröffnet und die betroffene Stelle lokalisiert.…”
Section: Persistierender Rechter Aortenbogen Mit Einem Linken Lig Arteriosumunclassified